Exosomes Derived from Human Primed Mesenchymal Stem Cells Induce Mitosis and Potentiate Growth Factor Secretion - Yuan, Oliver (Stem Cells Dev, 2019)
Mesenchymal stem cells (MSCs) facilitate functional recovery in numerous animal models of inflammatory and ischemic tissue-related diseases with a growing body of research suggesting that exosomes mediate many of these therapeutic effects. It remains unclear, however, which types of proteins are packaged into exosomes compared with the cells from which they are derived. In this study, using comprehensive proteomic analysis, we demonstrated that human primed MSCs secrete exosomes (pMEX) that are packaged with markedly higher fractions of specific protein subclasses compared with their cells of origin, indicating regulation of their contents. Notably, we found that pMEX are also packaged with substantially elevated levels of extracellular-associated proteins. Fibronectin was the most abundant protein detected, and data established that fibronectin mediates the mitogenic properties of pMEX. In addition, treatment of SHSY5Y cells with pMEX induced the secretion of growth factors known to possess mitogenic and neurotrophic properties. Taken together, our comprehensive analysis indicates that pMEX are packaged with specific protein subtypes, which may provide a molecular basis for their distinct functional properties.